2021
DOI: 10.1002/cncr.33909
|View full text |Cite
|
Sign up to set email alerts
|

Health plan‐based mailed fecal testing for colorectal cancer screening among dual‐eligible Medicaid/Medicare enrollees: Outcomes of 2 program models

Abstract: BACKGROUND:Health insurance plans are increasingly offering mailed fecal immunochemical test (FIT) programs for colorectal cancer (CRC) screening, but few studies have compared the outcomes of different program models (eg, invitation strategies). METHODS: This study compares the outcomes of 2 health plan-based mailed FIT program models. In the first program (2016), FIT kits were mailed to all eligible enrollees; in the second program (2018), FIT kits were mailed only to enrollees who opted in after an outreach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…More encouragingly, a recent study found that when dual Medicaid/Medicare enrollees are first called to see if they would like to be mailed a FIT test, the completion rate among those who expressed interest was 68%. 34 Further assessment of the reproducibility in an underserved population and scalability of this locally provided labor-intensive approach is needed before adoption as a broadly applicable strategy. Other interventions with FIT were found to be less effective in increasing screening rates.…”
Section: Discussionmentioning
confidence: 99%
“…More encouragingly, a recent study found that when dual Medicaid/Medicare enrollees are first called to see if they would like to be mailed a FIT test, the completion rate among those who expressed interest was 68%. 34 Further assessment of the reproducibility in an underserved population and scalability of this locally provided labor-intensive approach is needed before adoption as a broadly applicable strategy. Other interventions with FIT were found to be less effective in increasing screening rates.…”
Section: Discussionmentioning
confidence: 99%